Impact of lipid oxidization on vertical structures and electrostatics of phospholipid monolayers revealed by combination of specular x-ray reflectivity and grazing-incidence x-ray fluorescence - Korytowski, Agatha Anna; Abuillan, Wasim; Makky, Ali; Konovalov, Oleg; Tanaka, Motomu (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2015)
The influence of phospholipid oxidization of floating monolayers on the structure perpendicular to the global plane and on the density profiles of ions near the lipid monolayer has been investigated by a combination of grazing incidence X-ray fluorescence (GIXF) and specular X-ray reflectivity (XRR).
Gesehen am 22.07.2020